Mass Customization in Civil Construction - Machado, André Gustavo Carvalho; Moraes, Walter Fernando Araújo de (Review of Business Management, 2008)
The objective of this paper is to examine how the phenomenon of mass customization is being undertaken in the civil construction sector. Therefore, the research strategy adopted was a multiple-case study, which was carried through in two companies. The main technique adopted for the data collect consisted in semi-structured interviews. The analysis of the data occurred in five different phases. When analyzing the actions undertaken in the customization process, it was evidenced that the companies present different stages of customization. The use of technologies such as Drywall and PEX lead to customization and increase the flexibility of the facilities. The selection of suppliers and the enterprise of partnerships were also important. Clients demand qualified professionals, with wide vision of the business, apart from a strong integration between the technical and commercial areas. The core difficulties concern the non-accomplishment of deadlines for customization specifications and the high costs of the management of the productive system. It was possible to conclude that, less than mass customization; a pure customization strategy was adopted along with efforts associated to increase the flexibility of the project and of the construction. Key-words: Strategy. Mass customization. Civil construction.